Vestibular Dysfunction in Euthyroid Children with Hashimoto’s Thyroiditis - Gülcan Seymen; Gözde Günay; Ahmet Adnan Cirik; Reyhan Sürmeli; Mehmet Sürmeli (Journal of International Advanced Otology)
Background: A relationship exists between autoimmune thyroid disorders and vestibular dysfunction. This study aimed to analyze cervicalevoked myogenic potentials (cVEMP) and video head impulse test (vHIT) results between children with Hashimoto thyroiditis (HT) and healthy controls to determine vestibular end-organ problems.